Phytoremediation of leachate contaminated soil: a biotechnical option for the bioreduction of heavy metals induced pollution in tropical landfill - Barasarathi, Jayanthi (Springer Heidelberg, 2022)
Metal remediation is important considering the environmental pressure due to soil pollution from landfill leachate. Hence, identifying potential plant-based option for remediation, especially the use of bio-/hyper-accumulators, is inevitable. Contamination of soil with heavy metals has been a decades-long concern. This study is therefore aimed to evaluating the metal-remediation potentials of four ornamental plant species-Cordyline fruticosa, Duranta variegated, Tradescantia spathacea, and Chlorophylum comosum-on leachate-contaminated soil. Details of the study involved leachate analysis, soil characterization, and metal-accumulation test on selected plants. Characterization of both landfill soil and leachate has indicated that Pb, Cu, As, Mn, Cr, Zn, Fe, and Ni were higher than the prescribed limits. The high metal reduction efficiency of C. fruticosa on all the studied metals was about 63%, 85%, 77.88%, 77.55%, and 75% for Pb, As, Mn, Zn, and Cr concentrations. The metal removal by the plants was significantly higher as compared to control soil (P < 0.05). The highest removal rate constant witnessed was for Mn (0.023 day(-1)) and was achieved using C. fruticosa. The results have revealed that C. fruticosa was the most promising plant for the removal of the studied metals. Therefore, it can be concluded that C. fruticosa has potentials to remediate heavy metal-contaminated soil at significant level. The findings will develop investigation into plant-tissue and compartmentalization effect on metal remediation using C. fruticosa.